B2 Space occupying lesion in an HIV positive male- are common things always common?. (23rd May 2012) - Haidari, G; Singh, S; Freudenthal, B; Peters, B; Kulasegaram, R; Desai, M; Bodi, I
Abstract : A 62-year-old man with well controlled HIV infection presented to clinic in December 2011, with a 6 week history of increasing forgetfulness, unsteady gait and visual disturbance. He was well established on highly active antiretroviral therapy, with a CD4 count of 524 and an undetectable viral load. On examination his GCS was 15/15, and he was noted to have a homonymous hemianopia. MRI confirmed a large mass in the deep thalamus extending into the brainstem which did not typically enhance. He went on to have a brain biopsy confirming a high grade glioblastoma multiforme. Post biopsy he developed a dense right sided hemiplegia thought to be due to disease progression. There have been 21 case reports of glioblastoma multiforme in HIV, raising the possibility we are now seeing an increasing number in HIV positive patients. In all documented cases, HIV was not found in glial tumours, although it is thought the role of the immune system in glial cell transformation could be compromised in HIV. Discussion: HIV patients with glioblastoma multiforme are presenting at younger ages and have poorer outcomes than non-HIV patients. Glioblastoma multiforme should be considered in the differential for HIV patients presenting with neurological symptoms, especially in patients stable on highly active antiretroviral therapy with a good CD4 count, in an effort to reduce diagnostic delay.